Lymphadenectomy and pelvic irradiation in high-risk endometrioid endometrial cancer: a population-based retrospective analysis using the SEER databank - AmrA Soliman; Meike Schild-Suhren; SayedA Mostafa; Sarah Antar; Ahmed Nezzal; Basel Refky; Onur Güralp; Eduard Malik (Clinical and Experimental Obstetrics & Gynecology)
The current role of lymphadenectomy in early-stage high-risk endometrioid endometrial cancer is to guide further adjuvant treatment according to lymph node status. Whether the procedure has any therapeutic role remains controversial. In this study we aimed to investigate the outcome of current practices by performing a population-based retrospective cohort analysis using the US population-derived freely accessible public Surveillance, Epidemiology and End Results program (SEER) database. SEER data from patients with endometrial cancer treated between 2004 and 2012 were accessed online on March 1, 2016. Kaplan-Meier estimators were used to describe the survival distribution and the log-rank (Mantel-Cox) test was used to perform overall and pairwise comparisons of the survival distributions. The cohort included 47,463 patients, 10,288 of whom fulfilled high-risk criteria. A higher lymph node yield count was associated with better overall survival, although the removal of more than 40 lymph nodes did not confer any further survival benefit. The application of pelvic irradiation without lymph node status confirmation did not provide a survival benefit. From this analysis, no evidence of a survival benefit associated with lymphadenectomy was found. However, the current role lymphadenectomy as a staging and guiding tool for further adjuvant treatment was supported. Well-designed prospective randomized trials are required to conclusively determine the prognostic and therapeutic value of lymphadenectomy in patients with high-risk endometrioid endometrial cancers.